Biogeochemical markers across a pollution gradient in a Patagonian estuary: A multidimensional approach of fatty acids and stable isotopes - Kopprio, Germán Adolfo (2018)
A combined approach merging stable isotopes and fatty acids was applied to study anthropogenic pollution in the Río Negro estuary. Fatty acid markers of vegetal detritus indicated considerable allochthonous inputs at freshwater sites. Correlative evidence of diatom fatty acids, δ13C, chlorophyll and particulate organic matter suggested the importance of diatoms for the autochthonous organic matter production at the river mouth. Low δ15N values (~0‰) and high fatty acid 18:1(n-7) concentrations in the suspended particulate matter, in combination with the peaks of coliforms and ammonium, indicated a strong impact of untreated sewage discharge. The 15N depletion was related to oxygen-limited ammonification processes and incorporation of 15N depleted ammonium to microorganisms. This work demonstrates that the combined use of lipid and isotopic markers can greatly increase our understanding of biogeochemical factors and pollutants influencing estuaries, and our findings highlight the urgent need for water management actions to reduce eutrophication.